Series active variable geometry suspension: full-car prototyping and road testing - Yu,M; Cheng,C; Evangelou,S; Dini,D (IEEE-ASME Transactions on Mechatronics, 2021)
In this paper, afull-car prototype of the recently proposed mechatronic suspension, Series Active Variable Geometry Suspension (SAVGS), is developed for on-road driving experimental proof of concept, aiming to be adopted by suspension OEMs (original equipment manufacturers) as an alternative solution to fully active suspensions. Particularly, mechanical modifications are performed to both corners of the front double-wishbone suspensionof a production car, with active single-links attached to the upper-ends of the spring-damper units, while both corners of the rear suspension remain inthe original (passive) configurations.The mechanical modifications involve innovatively designed parts to enable the desired suspension performance improvements, while maintaining ride harshness at conventional levels.Areal-time embedded system is further developed to primarily implement:1) power supply, data acquisition and measurementsof the vehicle dynamics related variables, and 2) robust control application for the ride comfort and road holding enhancement, which is based on a derived linearized model of the full-car dynamics and a newly synthesizedH-infinity control scheme. Results obtained from on-road driving experiments are inessential agreement with numerical simulation results also produced. Overall, the full-car prototypeof SAVGS demonstrates promising suspension performance,with anaverage 3 dB attenuation (or equivalently 30% reduction) of the chassis vertical acceleration at aroundthe human-sensitive frequencies (2-5Hz),as compared to the original vehicle with the passive suspension system. More importantly, the prototype also indicatesthe practicality of the solution, as the SAVGS retrofit to a real car is achieved by simple mechanical modifications, compact actuator packaging, smallmass increment(21.5kg increase with respect to the original vehicle), limited power usage